Analysis of the Implementation of the Repair Business Development Strategy Using the Balanced Scorecard at PT PAL Indonesia: Analisis Implementasi Strategi Pengembangan Usaha Reparasi Menggunakan Balanced Scorecard pada PT PAL Indonesia - Abdul Honi; Rita Ambarwati S (Academia Open, 2021)
The shipbuilding industry, which is an economic support as a builder and maintenance of ships connecting areas between islands in Indonesia, is therefore needed in the face of an increasingly complex business environment such as today, a performance measurement method that can assess company performance accurately and thoroughly. In this case the method that can be used is the Balanced Scorecard. The purpose of using the Balanced Scorecard method is to measure company performance from four perspectives, namely: a growth and learning perspective, an internal business process perspective, a customer perspective, and a financial perspective. The author takes measurements at PT PAL Indonesia (Persero) using 2020 data to analyze financial perspectives, while for other perspectives using company data and questionnaire calculations distributed to PT PAL Indonesia (Persero) employees in the current year. From the results of the measurements that have been taken, it is known that the overall performance of PT PAL is quite good, this is indicated by the Scorecard value generated from each perspective. Accurate performance measurement results are very important for management, both in the planning, decision-making and control processes, as well as in realizing the company's vision and mission.